Potensi Ekstrak Rumput Kebar (Biophytum petersianum Klotzsch) Dalam Mempertahankan Jumlah Sel Sertoli Mencit (Mus musculus) Model Diabetes Melitus - Etik Yuliarini Widodo; Reny I’tishom; Bambang Purwanto (FORIKES, 2020)
Background: Hyperglycemia is a common effect of uncontrolled DM. The main impact of DM on male infertility is the result of hyperglycemia which causes an increasing in free radicals which cause oxidative stress in the testes, and then attacks Sertoli cells. Increasing of free radicals will cause disruption and damage to this cell, including apoptosis and atrophy and then caused decreasing in the number of Sertoli cells. Kebar grass contains antioxidants compounds, such as flavonoids and vitamin E. There are synergy effects between vitamin E and flavonoids which reinforce both in working to improve infertility as an antioxidant. Objective: To compared the number of Sertoli cells between groups which receiving extract kebar grass (Biophytum petersianum Klotzsch) and the control group in diabetes mellitus mice (Mus musculus) model. Methods: The research subjects used DM male mice which were divided into 5 groups: 2 control groups (K- and K+) and 3 treatment groups (P1, P2, P3). Day 1 to day 5, all groups were induced by STZ. The 11th day to the 45th day, the control group (K+) is given metformin 2 mg/head /day, the P1, P2 and P3 groups is given kebar grass with dose of 67,5; 135 and 270 mg/kg/day and metformin 2 mg/head/day. The 11th day to the 31th day, the control group (K-) is given CMC-Na 1% suspension. The 46th day is done surgery and sampling testicular tissue. Examination of the number of Sertoli cells is done through examination of the histological picture of testicular tissue that has been given Haematoxylin-Eosin (HE) staining. Results: Statistical tests showed that there was significant differences with a value of p = 0.000 (